The occurrence of discrimination in Croatia and citizens' awareness of anti-discrimination legislation - Bježančević, Sanja (Array, 2021)
The principle of non-discrimination is the foundation of the modern system of protection of human rights and freedoms and all the most important international legal treaties governing the protection of human rights proclaim this principle. As one of the fundamental values of the constitutional order of the Republic of Croatia, the prohibition of discrimination is regulated by the Anti-Discrimination Act. Although the legislative framework and mechanisms for protection against discrimination are satisfactory, the reality of discrimination is significantly different. A survey conducted on a sample of 761 adult respondents shows that discrimination is strongly present in Croatian society and that it affects women more often than men. In addition to gender, the sample was stratified by age, level of education, and employment status. These three categories indicated a significant effect on respondents’ awareness of the existence of the legislative framework for protection against discrimination. The chi-square test examined the correlation between the respondents’ awareness with the legislative framework and mechanisms of protection against discrimination and their treatment as victims of discrimination. The results of the research show that distrust in the system and state institutions is the main reason for nonaction by victims of discrimination, which clearly shows the need for stronger commitment of all stakeholders and the creation of a comprehensive system of protection against discrimination.